2012
DOI: 10.1063/1.3680022
|View full text |Cite
|
Sign up to set email alerts
|

Gender bias in the force concept inventory?

Abstract: Could the well-established fact that males tend to score higher than females on the Force Concept Inventory (FCI) be due to gender bias in the questions? The eventual answer to the question hinges on the definition of bias. We assert that a question is biased only if a factor other than ability (in this case gender) affects the likelihood that a student will answer the question correctly. The statistical technique of differential item functioning allows us to control for ability in our analysis of student perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
33
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 4 publications
7
33
1
Order By: Relevance
“…The Sample 1 results of this study supported the advantage for women in item 9 found in Deitz et al [56] (large DIF) and Osborn Popp et al [47] (small to moderate DIF). This study also supported the large DIF toward men of item 23 found in both of these previous studies.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The Sample 1 results of this study supported the advantage for women in item 9 found in Deitz et al [56] (large DIF) and Osborn Popp et al [47] (small to moderate DIF). This study also supported the large DIF toward men of item 23 found in both of these previous studies.…”
Section: Discussionsupporting
confidence: 81%
“…4 of Ref. [56] it seems likely item 15 would be found biased towards women and items 12, 14, and 27 biased towards men, consistent with this work. The graph also suggests item 30 may also be biased toward men.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The inventory's questions have been investigated using many methods, notably through differential item functioning (Dietz, Pearson, Semak, & Willis, 2012) and alternative question construction (McCullough & Meltzer, 2001). Both studies gave evidence that the FCI had questions that favoured one gender over the other, but neither were able to conclude firmly how students of a certain gender would be affected by a certain question.…”
mentioning
confidence: 99%